Chinese and Russian Language Equivalents of the IAU Gazetteer of Planetary Nomenclature: an Overview of Planetary Toponym Localization Methods. (2nd October 2019) - Hargitai, Henrik; Li, Chunlai; Zhang, Zhoubin; Zuo, Wei; Mu, Lingli; Li, Han; Shingareva, Kira B.; Shevchenko, Vladislav Vladimirovich
ABSTRACT: The Gazetteer of Planetary Nomenclature (GPN) is maintained by the International Astronomical Union Working Group for Planetary System Nomenclature. It contains the internationally approved forms of place names of planetary and lunar surface features. In the last decades, spacefaring and other nations have started to develop local standardized equivalents of the GPN. This initiated the development of transformation methods and created a need for auxiliary information on the names in the GPN that is not available from the database of the GPN. The creation of 'localized' (local language) variants of the GPN in non-Roman scripts is an unavoidable necessity, but is also a cultural need. This paper investigates the localization methods into Chinese and Russian; two nations with different scripts, and two that are spacefaring ones. The need for the creation of a localized GPN is related to the local importance of scientific papers published in the local language and the existence of locally developed and operated scientific planetary spacecraft, but exceptions exist.